Does slack influence public and private labor market interactions? - Lamo, Ana; Moral-Benito, Enrique; Pérez, Javier J. (Frankfurt am Main, 2016)
"We empirically analyze the impact of public employment and wages' shocks on private labor market outcomes by studying if policies operate differently in periods of economic slack than in normal times. We use local projection methods and focus on the Spanish and euro area aggregate cases. We find that the degree of economic slack is key to determine: (i) if public employment crowds-out private employment, and (ii) the degree and extent of public wage influence on the private sector. In addition, we find that the specific features of the economy also count. In the case of Spain, when fiscal consolidation is implemented at times of economic distress, the contractionary effects of public employment cuts appear more damaging for the economy than those of public wage cuts, while the opposite happens for the euro area as a whole. These differences are likely to be related to specific features of the labor markets in both cases."